Rendimento dos componentes não integrantes da carcaça de ovinos alimentados com dietas de alto grão - Batista, Nayane Valente (Universidade Federal Rural do Semi-Árido, 2017)
The non-carcass components, represent an important source of protein in human nutrition, mainly in the region of the brazilian northeast, a better organization of the sheep chain would allow constant access and greater security to these by-products. The objective of this study was to determine the yield of viscera and organs of sheep fed high grain diets with three concentrated proportions: bulky (100; 80:20; 60:40). 24 lambs males, uncastrated, SPRD, confined to collective bays for 52 days were used. The diet was composed of tifton hay and the portion concentrated by 85% of whole grain corn and 15% of pelleted commercial supplement. At the end of the experiment, the animals were slaughtered and eviscerated, obtaining the weights of the non-integral components of the carcass. For organ and viscera yield the weights were adjusted for slaughter weight (PCA). For the statistical analysis, the statistical package SAS (2004) was used, and the data submitted to analysis of variance and the averages compared by the Tukey test, at 5% of significance. There was no significant effect of diets for consumption, total weight gain, slaughter weight. For skin and heart superior results were obtained in the diets with 100% concentrate. In the 60% diet the weights of lungs, TGI and buchada yield were higher.
Monografia
Keywords: Buchada; Pele; Subprodutos da ovinocultura; Vísceras comestíveis; Buchada; Edible viscera; Sheep by-products; Skin; CIENCIAS AGRARIAS::ZOOTECNIA